Vliv osobnostních a demografických charakteristik zákazníků na jejich loajalitu - Suchánek, Petr; Činčalová, Simona; Prokop, Martin (University of Pardubice, 2019)
The paper deals with the influence of several personal factors on customer loyalty, which is one of the main tools of the company´s competitiveness. The aim of the article is to find out whether there is a relationship between selected personality and demographic characteristics and customer loyalty. The research was conducted on a sample of 1530 customers (final consumers) from 102 food industry companies in the Czech Republic. The research was conducted using a cross-comparison method with relevant statistical tests. Research results show that customer loyalty is related to the demographic characteristics examined (especially gender, income and education) and some personality traits (especially the approach to buying cheap things and optimism). Research shows that women are more loyal than men, then optimists and people who are not so rich that they can buy cheap things. On the contrary, with increasing income and education loyalty is rather falling.
The influence of customer´s personal and demographic characteristics on their loyalty
Keywords: customer´s loyalty; demographic characteristics; personal characteristics; food industry; L66; M31